Day hiking. North Cascades - Romano, Craig (Mountaineers Books, 2020)
"This guide describes 136 hikes in the North Cascades, including Mount Baker, the North Cascades Highway, Methow Valley, and the Mountain Loop Highway. This second edition will feature full-color photographs and fully updated hike descriptions and maps, as well as 30 all-new hikes"--